The moderating role of coping styles on the associations of fatigue with life satisfaction in Chinese nurses: a cross-sectional study - Yuekun Wu; Wen Bo; Mengyao Li; Li Liu; Hui Wu (BMC, 2024)
Abstract Background Fatigue affects nurses negatively and may influence life satisfaction. According to the stress process model, active coping might influence the impact of adverse conditions such as fatigue on well-being measures such as life satisfaction. However, no research examined the associations among nurses' fatigue, coping styles, and life satisfaction. Methods The cross-sectional study was conducted in Liaoning Province, China. 482 effective questionnaires were collected (effective response rate of 80.3%). The questionnaire included Fatigue Scale-14, Simplified Coping Style Questionnaire and Satisfaction with Life Scale. The association among fatigue, coping styles and fatigue × coping styles interaction with life satisfaction was examined by hierarchical multiple regression analysis. The interaction was visualized by simple slope analysis. Results Mean score of life satisfaction was 22.74 ± 6.11. Active coping moderated the relationship between mental fatigue and life satisfaction. The impacts of mental fatigue on life satisfaction gradually decreased in the low (1 SD below the mean, β=-0.400, P < 0.001), mean (β=-0.312, P < 0.001), and high (1 SD above the mean, β=-0.224, P < 0.001) groups of active coping. Conclusion The life satisfaction of Chinese nurses was relatively low. Active coping could alleviate the impact of mental fatigue on life satisfaction. Developing active coping styles might be a crucial strategy to alleviate nurses' mental fatigue and improve life satisfaction.